2004
DOI: 10.1186/1471-2105-5-150
|View full text |Cite
|
Sign up to set email alerts
|

PCOGR: Phylogenetic COG ranking as an online tool to judge the specificity of COGs with respect to freely definable groups of organisms

Abstract: Background: The rapidly increasing number of completely sequenced genomes led to the establishment of the COG-database which, based on sequence homologies, assigns similar proteins from different organisms to clusters of orthologous groups (COGs). There are several bioinformatic studies that made use of this database to determine (hyper)thermophile-specific proteins by searching for COGs containing (almost) exclusively proteins from (hyper)thermophilic genomes. However, public software to perform individually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…All new sequences were submitted to NCBI GenBank (accession numbers from GQ214060 to GQ214077). After analysing the entire fragment variability in MEGA 3.1 (Kumar et al 2004), we selected a short fragment of the first exon, which revealed high interspecific diagnostic polymorphism, thus showing great potential to easily and reliably identify all species. This region was also selected because lower intraspecific variation is likely to occur in exons, when compared to intronic regions or other non-coding fragments.…”
Section: Methodsmentioning
confidence: 99%
“…All new sequences were submitted to NCBI GenBank (accession numbers from GQ214060 to GQ214077). After analysing the entire fragment variability in MEGA 3.1 (Kumar et al 2004), we selected a short fragment of the first exon, which revealed high interspecific diagnostic polymorphism, thus showing great potential to easily and reliably identify all species. This region was also selected because lower intraspecific variation is likely to occur in exons, when compared to intronic regions or other non-coding fragments.…”
Section: Methodsmentioning
confidence: 99%
“…All haplotypes identified here have been deposited in GenBank (Accession numbers FJ596283-FJ596287). DNA sequences were aligned with the CLUSTALW algorithm implemented in MEGA 3.1 (Kumar et al 2004). MEGA was also used to identify identical haplotypes, to assess the presence and consistency of diagnostic sites between the two species, and to perform phylogenetic analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The full length gene sequence of cyt b and a partial sequence of the 16S rDNA gene and the D-loop mitochondrial region were analyzed separately for genetic distance and character-based variations using the MEGA 3.1 computer package (Kumar et al 2004) and PAUP (version 4b10) (Swofford 1998), respectively. The obtained sequences were aligned using Clustal X (version 1.83) and phylogenetic distances were calculated according to Kimura (1980) or/and Jukes and Cantor (1969) methods.…”
Section: Sequencing and Data Analysismentioning
confidence: 99%